ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROBABILITAS STOCK HIT LIMIT PADA PERUSAHAAN YANG LISTING DI BEI (BURSA EFEK INDONESIA) - Azizah Ali, Antin; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2015)
This study examine the factors that affect probability stock hitting the limit. The purpose of this study was to determine how much influence the beta, book to market value, firm size, and trading volume activity against the probability of stock hit limit on company listed on the Indonesia Stock Exchange. The analysis technique used is maximum likelihood, logit regression, and hypothesis testing using nagelkerke R square. The result are (1) beta has negative significant impact to probability stock hit up limit, but it has no significant impact to probability stock hit down limit. (2) book to market value has negative significant impact to probability stock hit up limit, but it has no significant impact to probability stock hit down limit. (3) firm size has negative signifikan impact both on probability stock hit up limit and down limit. (4) trading volume activity has positive significant impact to probability stock hit up limit but it has no significant impact to probability stock hit down limit.